Relaciones interpersonales y liderazgo de socias del club de madres “Estrellita de Jesús”-Sector Río Seco- distrito El Porvenir: 2018. - Cieza Sifuentes, Lizette Karen (2019)
The present research work was carried out with the purposeof publicizing the interpersonal relationships and leadership that exists within the "Estrellita de Jesús" mothers' club in the dry river sector of the El Porvenir district: 2018. The type of applied research has been considered, based on an explanatory design, and the sample consisted of 30 members, with whom we worked applying the methods and techniques of quantitative and qualitative research. The mothers' club "Estrellita de Jesus" is a grassroots organization that was created with the purpose of providing food support through the delivery of food to a population considered vulnerable, with the purpose of helping to overcome food insecurity in which are women, children and the elderly. However, here there are deficient interpersonal relationships that are weakening their level of communication within the organization, a situation that affects the fulfillment of their organizational objectives and goals. Finally, we recommend that training programs be developed to improve their interpersonal relationships, their level of leadership, teamwork and level of communication; to improve its management by providing a quality service to the beneficiaries and members of the "Estrellita de Jesús" mothers club.